The effectiveness of palm oil fuel ash in preventing expansion due to alkali-silica reaction - Abdul Awal, A. S. M.; Hussin, M. Warid (Elsevier Science Ltd, 1997)
Laboratory tests were conducted to evaluate the performance of palm oil fuel ash (POFA), a recently identified pozzolanic material, in reducing the e.xpansion of mortar bars containing Tuff as a reactive aggregate where ordinary Portland cement (OPC) was replaced, mass for mass, by 0, 10, 30 and 50% POFA. The South Ajiican NBRI Accelerated Test method was used in the experimental investigation, which revealed that palm oil fuel ash has a good potential in suppressing expansion due to alkali-silica reaction.